Romana Newton

2022-02-25

$\frac{1-\mathrm{tan}\left(\frac{x}{2}\right)}{1+\mathrm{tan}\left(\frac{x}{2}\right)}=\frac{1-\mathrm{sin}x}{\mathrm{cos}x}=\frac{\mathrm{cos}x}{1+\mathrm{sin}x}$

King Osborn

I'm doing it from RHS
$\frac{1-\mathrm{tan}\left(\frac{x}{2}\right)}{1+\mathrm{tan}\left(\frac{x}{2}\right)}=\frac{1-\mathrm{sin}x}{\mathrm{cos}x}=\frac{\mathrm{cos}x}{1+\mathrm{sin}x}$
$=\frac{\mathrm{cos}x}{1+\mathrm{sin}x}$
$=\frac{\frac{1-{\mathrm{tan}}^{2}\left(\frac{x}{2}\right)}{1+{\mathrm{tan}}^{2}\left(\frac{x}{2}\right)}}{1+\frac{2\mathrm{tan}\left(\frac{x}{2}\right)}{1+{\mathrm{tan}}^{2}\left(\frac{x}{2}\right)}}$
$=\frac{\frac{1-{\mathrm{tan}}^{2}\left(\frac{x}{2}\right)}{1+{\mathrm{tan}}^{2}\left(\frac{x}{2}\right)}}{1+\frac{2\mathrm{tan}\left(\frac{x}{2}\right)}{1+{\mathrm{tan}}^{2}\left(\frac{x}{2}\right)}}$
$=\frac{1-{\mathrm{tan}}^{2}\left(\frac{x}{2}\right)}{1+{\mathrm{tan}}^{2}\left(\frac{x}{2}\right)+2\mathrm{tan}\left(\frac{x}{2}\right)}$
$=\frac{\left(1-\mathrm{tan}\left(\frac{x}{2}\right)\right)\left(1+\mathrm{tan}\left(\frac{x}{2}\right)\right)}{{\left(1+\mathrm{tan}\left(\frac{x}{2}\right)\right)}^{2}}$
$=\frac{\left(1-\mathrm{tan}\left(\frac{x}{2}\right)\right)}{1+\mathrm{tan}\left(\frac{x}{2}\right)}\right\}$
$=LHS$

Do you have a similar question?